Análise das estratégias de preservação do acervo em disco de vinil na fonoteca Satyro de Mello - GUIMARÃES, Maria de Nazaré da Silva (2021)
Study about the preservation of vinyl records, based on a case study carried out at the Fonoteca Satyro de Mello, located at the Cultural Foundation of the State of Pará. The research objectives was to verify the preservation practices adopted for the vinyls of this collection. The research covered concepts about special file, sound documents and preservation of documents, as well as the evolution, characteristics, and conservation strategies of the vinyl disc. The research is methodologically characterized as a case study, interviewing the professionals responsible from collection. Based on the information collected, it was possible to verify that the library has cleaning and storage measures that are in accordance with the preservation of this support, thus allowing the extension of it is useful life and that the users have access to this material. On the other hand, it has been found that there is a lack of a plan documentary preservation drawn up for the collection of vinyls, and that the air conditioning of the environment is not yet properly stable, and these are questions for future suggestions.